PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI ISLAM DI MADRASAH IBTIDAIYAH - Aziz, Ayka; Hasanah, Uswatun (CV. Gerasi Insan Nusantara, 2022)
Indications of weak character are found in several cases. Efforts to build national character is carried out by the Ministry of Education and Culture through establishing six “profil pelajar Pancasila” that are trying to be developed in students so they become lifelong learners, have global competence, and behave according to Pancasila values. The study aims to describe the implementation of character education based on Islamic values in realizing the “profil pelajar Pancasila”. The method used is qualitative research. The study was conducted at MI Barokah at-Tahdzib Kras Kediri. Data were obtained through in-depth interviews with informants: principals, heads of infrastructure, and homeroom teachers; observation; and document studies. Data analysis was carried out using the following steps: data reduction, data presentation, and drawing conclusions. The results of the study shows: 1) Islamic values that are implemented include: cleanliness and purity of the soul, piety, morality, and the qurani which have complete unity and become the basis for madrasah to carry out character education; 2) Implementation of character education based on Islamic values is emphasized on habituation, such as: speaking in Javanese krama inggil, calling teachers ustaz/ustazah, shaking hands, learning Quran using the Yanbu'a method, memorizing the Kaifa Tusholli, memorizing prayers, tahfiz, reading Ngudi Susilo's book, praying Duha and Zuhur together; 3) The Pancasila student profile is realized by: ubudiah activities, providing religious understanding, exemplary, directives, as well as habituation and coaching in accordance with each “profil pelajar Pancasila”